2015
DOI: 10.1371/journal.pone.0118287
|View full text |Cite
|
Sign up to set email alerts
|

Sarsaparilla (Smilax Glabra Rhizome) Extract Inhibits Migration and Invasion of Cancer Cells by Suppressing TGF-β1 Pathway

Abstract: Sarsaparilla, also known as Smilax Glabra Rhizome (SGR), was shown to modulate immunity, protect against liver injury, lower blood glucose and suppress cancer. However, its effects on cancer cell adhesion, migration and invasion were unclear. In the present study, we found that the supernatant of water-soluble extract from SGR (SW) could promote adhesion, inhibit migration and invasion of HepG2, MDA-MB-231 and T24 cells in vitro, as well as suppress metastasis of MDA-MB-231 cells in vivo. Results of F-actin an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 46 publications
(62 reference statements)
0
15
0
Order By: Relevance
“…(SRG, genus: Smilax ), the dried rhizome of Sarsaparilla, also called Tu-Fuling in Chinese medicine, is commonly used as the complementary therapy in the Orient for various chronic diseases, including RA, diabetes, liver deficiency, coronary heart, and syphilis [ 10 ]. It is officially included in the Chinese Pharmacopeia and has been investigated for its antivirus, antioxidant, anticancer, and anti-inflammation properties [ 11 – 13 ]. SRG is classified into two categories based on its cross-sectional color, red SGR or white SGR, and the investigation of their chemical composition indicates significant difference in the quality correlating to their color metrics [ 10 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(SRG, genus: Smilax ), the dried rhizome of Sarsaparilla, also called Tu-Fuling in Chinese medicine, is commonly used as the complementary therapy in the Orient for various chronic diseases, including RA, diabetes, liver deficiency, coronary heart, and syphilis [ 10 ]. It is officially included in the Chinese Pharmacopeia and has been investigated for its antivirus, antioxidant, anticancer, and anti-inflammation properties [ 11 – 13 ]. SRG is classified into two categories based on its cross-sectional color, red SGR or white SGR, and the investigation of their chemical composition indicates significant difference in the quality correlating to their color metrics [ 10 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Astilbin, 3,3,4′,5,7-pentahydroxyflavanone 3–6[-deoxy-([alpha]-L-mannopyranoside)], is one of the major active components in the rhizome of SGR. This flavonoid shows multiple pharmacological functions, such as migration of ear contact dermatitis and liver injury induced by delayed-type hypersensitivity associated with selective immunosuppression of activated T lymphocytes or dysfunction of liver-infiltrating cells [ 13 , 16 , 17 ]. Nevertheless, the direct role of astilbin, isolated from GZ-SGR extract, in the treatment of inflammatory disease such as RA, is still unclear and the mechanistic basis is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…In conclusion, to the best of our knowledge, the present study demonstrated for the first time the potential benefits of co-administration of MTX with SGR. Co-administration of SGR may be beneficial for therapy of lung cancer and splenic carcinoma, osteosarcoma, and liver diseases, but may reduce the therapeutic effect of treating cancer in the digestive tract, systemic lupus erythematosus and psoriasis (50)(51)(52)(53)(54). The herb-drug interaction may be associated with the activity change of transporters.…”
Section: Discussionmentioning
confidence: 99%
“…Pictures of the marked gap were taken at 24 h and 48 h after the gaps were created. The wound gaps (in mm) were quantified by using image‐pro plus software and calculated by the equation: % migration distance = (gap 0 h treated− gap 24 h or 48 h treated )/(gap 0 h control− gap 24 h or 48 h control ) * 100% .…”
Section: Methodsmentioning
confidence: 99%